Numerical and experimental studies of homogeneous charge compression ignition engine performance - Najafabadi, Mohammad Izadi (2014)
During the recent decade, an alternative combustion technology, known as Homogeneous Charge Compression Ignition (HCCI), has shown the potential to decrease both emissions and fuel consumption. In spite of its high fuel efficiency and low NOx emission compared to diesel and SI engines, HCCI combustion has some critical difficulties. The main difficulty of HCCI engine is the absence of any external control of ignition timing. Finding the effects of different parameters on the ignition timing is vital to be able to control HCCI engines. The focus of this study was to carry out a detailed numerical and experimental investigation into the factors affecting HCCI ignition timing in a 2-stroke gasoline engine. As the primary objective of this study, a Computational Fluid Dynamic (CFD) model was developed coupled to a semi-detailed chemical mechanism for the 2-stroke engine to investigate the effects of different variables such as intake temperature, air to fuel ratio, scavenging efficiency, and compression ratio on the ignition timing and emissions. As the second objective, effects of different simulation parameters such as turbulence model, grid density, and time step size were investigated to find the best method for simulation of considered engine. As the final objective, validation of numerical results was carried out using experimental study on the 2-stroke engine that was modified to operate in HCCI mode. Results confirmed that k-ε RNG model was the best turbulence model for simulation of this case study coupled to the time step size of 0.25 crank angle degree and the grid size of around 50,000 cells. Results also demonstrated that decreasing the intake temperature,equivalence ratio, residual gasses, and compression ratio can significantly retard the combustion timing and experimental results confirmed that this ignition retarding can considerably increase the engine power and torque.